2017
DOI: 10.1097/ccm.0000000000002189
|View full text |Cite
|
Sign up to set email alerts
|

Higher Fluid Balance Increases the Risk of Death From Sepsis: Results From a Large International Audit*

Abstract: In this large cohort of patients with sepsis, higher cumulative fluid balance at day 3 but not in the first 24 hours after ICU admission was independently associated with an increase in the hazard of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
177
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(195 citation statements)
references
References 24 publications
6
177
1
11
Order By: Relevance
“…In line with this, recent experimental data suggested that fluid resuscitation preceding the start of vasopressors is associated with higher lactate levels and a paradoxical increase in vasopressor requirements when compared with an immediate start of vasopressor therapy without previous fluid administration [11]. Likewise, a number of observational studies suggest that the volume of resuscitation fluids and net fluid balance is associated with mortality in sepsis [12][13][14][15][16][17][18][19][20][21][22][23][24]. Nevertheless, other data indicates that vasopressors should be administered in combination with fluids since isolated vasopressors can improve arterial pressure but not regional blood flow [25].…”
Section: Introductionmentioning
confidence: 89%
“…In line with this, recent experimental data suggested that fluid resuscitation preceding the start of vasopressors is associated with higher lactate levels and a paradoxical increase in vasopressor requirements when compared with an immediate start of vasopressor therapy without previous fluid administration [11]. Likewise, a number of observational studies suggest that the volume of resuscitation fluids and net fluid balance is associated with mortality in sepsis [12][13][14][15][16][17][18][19][20][21][22][23][24]. Nevertheless, other data indicates that vasopressors should be administered in combination with fluids since isolated vasopressors can improve arterial pressure but not regional blood flow [25].…”
Section: Introductionmentioning
confidence: 89%
“…Patients with higher net positive fluid balances consistently experienced higher mortality. 915 While these results provide rationale for questioning the safety of large volume fluid boluses and pursuing interventional trials, the high risk of confounding in these observational studies precludes a causality assessment or defining an optimal clinical approach. 55,56 Severity of illness is a strong potential confounder in the association between volume of fluid administration (and net fluid balance) and mortality, because more severely ill septic patients tend to receive more IVF during routine clinical care.…”
Section: Restrictive Fluids Approachmentioning
confidence: 99%
“…15 However, an improved mechanistic understanding of potential harm from excessive fluid administration 68 and emerging observational data associating positive fluid balance with higher mortality 915 have recently challenged the paradigm of large-volume fluid resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with these pathophysiologic mechanisms, an accumulating body of evidence has established positive fluid balance as a strong and independent predictor of poor outcomes in the critically ill. [26][27][28] For example, a large international study on more than 1800 patients with sepsis found that a higher cumulative fluid balance 3 days after ICU admission was proportionately associated with an increased risk of death. 29 Similarly, the Sepsis Occurrence in Acutely Ill Patients (SOAP) study on more than 1100 patients with sepsis from 198 European ICUs reported positive fluid balance as an independent risk factor for mortality. 30 Further supporting this notion is the observation that achieving a negative fluid balance in volume-overloaded patients with sepsis is associated with improvement in survival rates.…”
Section: Acquired Volume Overloadmentioning
confidence: 99%